Research on the Reciprocating Sealing of Fracturing Pump - Wei Bing Zhu; Gang Zhou; He Shun Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
The failure reasons of reciprocating sealing in OPI-1800AWS fracturing pump are analyzed by scanning electron microscope technology (SEMT). The lubrication mechanism of plunger seal friction pair is analyzed by hydrodynamic lubrication theory. During its discharge and suction stroke, the reciprocating sealing friction pair meets the conditions of hydrodynamic lubrication, a certain thickness of oil film can be formed and maintained between the plunger and V-shaped sealing interface, which can lubricate sealing pair, reduce friction and improve lifetime. The axial pressure distribution of the V-shaped sealing is carried out by theoretical analysis and experimental testing. According to the distribution curve of axial pressure, the V-shaped sealing failure and the determination of the number of loops are discussed.